rac-2-{3-[1-(Acetyloxy)ethyl]-2,2-dimethylcyclobutyl}acetic acid - Dieter Schollmeyer; Paul Jirsch; Heiner Detert (IUCrData)
The title compound, C12H20O4, was prepared from α-pinene in three steps. The ester and acid moieties are cis on the slightly folded cyclobutane ring. In the crystal, carboxylic acid bound dimers form layers parallel to (202).